PENGARUH KOMBINASI LATIHAN PUSH UP DAN FOLLOW THROUGH DENGAN METODE MARYLAND 5 POST SHOOTING DRILL TERHADAP KEMAMPUAN SHOOTING 3 POINT - Wijayanto, Octa Pratama; Hilmawan Wismanadi; Hijrin Fitroni; Muhammad Dzul Fikri (Jayabama: Jurnal Peminat Olahraga, 2024)
ABSTRACTSThe game of basketball is attractive and dynamic because it plays the ball in various ways, namely dribbling, passing, shooting, and layups. Basketball aims to enter the ball as much as possible and also keep the ring from being entered by the opponent's ball. The development in playing basketball in the current era is very different where each player is required to be able to score 3 points to break the deadlock if the game system is not running well. Where to take a shot in a basketball game requires complex movements. The purpose of this study was to analyze the effect of a combination of push-ups and follow-through exercises on the 3-point shooting ability of students in extracurricular basketball at Junior High School 1 Kediri. The research was conducted on 24 students who are members of the basketball team at Junior High School 1 Kediri. The type of research used in this study used a quantitative approach and the design used was two group Pretest-Posttest Design. The data analysis technique used in this study is a preliminary test involving normality test and homogeneity test, as well as hypothesis testing. The results showed that after being treated with a combination of push-up and follow-through exercises in group A, an increase of 2.75 was obtained in the average score with a value of 6.333 to 9.25. When compared to group B which was not treated with a combination of push-up and follow-through exercises, it only increased by 0.084 with an average score of 6.416 to 6.5. These results indicate that the success of students' 3-point shooting requires a training process that is not easy but is calculated to be effective in the success of shooting 3 points. This study concludes that there is an influence in the combination of push-up and follow-through exercises on the ability to shoot 3 points on the Junior High School 1 Kediri basketball team.KEYWORD: Basketball, shooting, follow through, and push up